Ratking - Dibdin, Michael, 1947-2007 (faber and faber, 1999)
Police Commissioner Aurelio Zen has crossed swords with the establishment before - and lost. But from the depths of a mundane desk job in Rome he is unexpectedly transferred to Perugia to take over an explosive kidnapping case involving one of Italy's most powerful families.